2010
DOI: 10.1007/s10722-010-9605-1
|View full text |Cite
|
Sign up to set email alerts
|

ODAP levels in some Lathyrus species distributed on Burdur-Isparta provinces in Turkey

Abstract: Lathyrus species are distributed in natural areas of Turkey and are cultivated for use in human and animal food. Plants and seeds of Lathyrus species contain a neurotoxic substance called b-N-oxalyl-La, b-diamino propanoic acid (ODAP). When consumed in large quantities, ODAP may cause a kind of paralysis known as lathyrism. In this note, ODAP levels were determined in Lathyrus species collected in the Burdur-Isparta provinces. The leaves and seeds of plant samples were analysed using High Performance Liquid Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…In the present study, β-ODAP contents of the samples were between 0.20 and 1.18 mg/g. Karadeniz et al (2010) found that there was no β-ODAP in the seeds of L. aphaca, L. sphaericus and L. aureus and β-ODAP levels of L. cicera L. and L. clymenum L. seeds were 0.053 and 0.171%, respectively. Basaran et al (2016) reported the β-ODAP contents in 52 L. sativus seeds varied from 2.62 mg/g up to 5.59 mg/g.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the present study, β-ODAP contents of the samples were between 0.20 and 1.18 mg/g. Karadeniz et al (2010) found that there was no β-ODAP in the seeds of L. aphaca, L. sphaericus and L. aureus and β-ODAP levels of L. cicera L. and L. clymenum L. seeds were 0.053 and 0.171%, respectively. Basaran et al (2016) reported the β-ODAP contents in 52 L. sativus seeds varied from 2.62 mg/g up to 5.59 mg/g.…”
Section: Resultsmentioning
confidence: 91%
“…In the study, the mean protein content of Lathyrus taxa was 26.15% (Table 5). It was reported that some cultivars of L. cicera grown in Turkey are as high in nutritional value as soybeans (Karadeniz et al, 2010). In previous study, Pastor-Cavada et al (2011) determined that protein contents of 15 Lathyrus species fall within the range of 17.7 and 25.6%.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We investigated RSAs of some Lathyrus taxa which we determined ODAP contents of. In our previous study, some Lathyrus species such as L. cicera which has relatively larger and lighter coloured seeds contain ODAP while L. sphaericus and L. aphaca having antioxidant activity, did not contain ODAP [10]. More studies are needed on Lathyrus' neurotoxins and secondary metabolism and genetic and environmental effects on them.…”
Section: Resultsmentioning
confidence: 93%
“…Fiori in Fiori & Paol. and L. setifolius L., distributed in Burdur-Isparta regio which we determined ODAP content of in our previous study [10]. [11] (Table 1).…”
Section: Introductionmentioning
confidence: 99%